ANALISIS STRATEGI REKRUTMEN CALEG DPRD PARTAI AMANAT NASIONAL DI DKI JARKATA: PENCALONAN ASTRID KUYA - Abdul Ghofur; Pradita, Ragilia Dwi; Silvana Putri Priageng; Rahma Apasha; Fattiha Syanira Nirmala Amantha; Zenab Farisa; Shella Shofiana; Charren Galuh Indraswari; Nasikh Bilahi Fahmi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the strategies used by the National Mandate Party (PAN) in recruiting legislative candidates for the Regional People’s Representative Council (DPRD). This research employs a descriptive qualitative approach with data collection techniques based on literature studies. The focus of the study is to understand PAN’s legislative candidate recruitment strategy through the nomination of Astrid Kuya. The findings reveal that Astrid Kuya’s candidacy reflects PAN’s recruitment strategy based on the candidate’s popularity. The popularity of a candidate serves as a significant political asset. This is evident in how Astrid Kuya’s public appeal contributed to PAN’s success in the election. Her popularity proved to be a strong factor in attracting voters. Keywords: Astrid Kuya, Political Party, Popularity, Recruitment